Metabolic Engineering Towards the Enhancement of Photosynthesis - Peterhansel, Christoph; Niessen, Markus; Kebeish, Rashad M. (Photochemistry and photobiology, 2008)
Photosynthetic capacity is a promising target for metabolic engineering of crop plants towards higher productivity. Crop photosynthesis is limited by multiple factors dependent on the environmental conditions. This includes photosynthetic electron transport, regeneration of CO2 acceptor molecules in the reductive pentose phosphate cycle, the activity and substrate specificity of the CO2‐fixing enzyme Ribulose‐1,5‐bisphosphate carboxylase/oxygenase, and the associated flow through the photorespiratory pathway. All these aspects of the photosynthetic network have been the subject of recently published metabolic engineering approaches in model species. Together, the novel results raise hopes that engineering of photosynthesis in crop species can significantly increase agricultural productivity.